THE FORFAITING: AN OPTION TO FINANCING THE TRADE INTERNATIONAL - Del Carpio Gallegos, Javier (2005)
Forfaiting is the discount of accounts to receive related to transactions of Trade International, without resource for the exporter. The Forfaiting consist in letters purchase of credit of export and/or collections guaranteed. In one transaction forfaiting, the exporter decides to give the rights that demand for the payment of merchandise or services given to an importer under contract of sale, in exchange for a payment in cash of a bank forfaiting.